Power Quality Signals Detection Using S-Transform - ahmad, Nur Hafizatul Tul Huda; Abdullah, Abdul Rahim; JOPRI, MOHD HATTA (2013)
Power quality has become very important issue over the last decade. Poor quality can cause equipment failure, data and economical. An automated monitoring system is needed to ensure signal quality, reduces diagnostic time and rectifies failures. In this paper, S-transform is used to analyze the power quality signals such as swell, sag, interruption, harmonic, interharmonic and transient based on IEEE Std. 1159-2009 to detect, localize and classify the disturbance. The S-transform is used to represent the signals in time-frequency representation (TFR). ).To get an accurate TFR, the parameters are estimated to identify the signal characteristics. The signal characteristics are the root means square voltage (Vrms), total harmonic distortion (THD), total non harmonic distortion (TnHD) and total waveform distortion (TWD). To verify the performance of Stransform several sets of data with different time duration are analyzed to determine the accuracy of S-transform. The lowest value of mean absolute percentage error (MAPE) gives the highest accuracy to provide the best performance of TFD.